2006
DOI: 10.1128/jb.01253-06
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aggregatibacter ( Actinobacillus ) actinomycetemcomitans Leukotoxin Secretion by Iron

Abstract: The gram-negative oral and systemic pathogen Aggregatibacter (Actinobacillus) actinomycetemcomitans produces a leukotoxin (LtxA) that is a member of the RTX (repeats in toxin) family of secreted bacterial toxins. We have recently shown that LtxA has the ability to lyse erythrocytes, which results in a beta-hemolytic phenotype on Columbia blood agar. To determine if LtxA is regulated by iron, we examined beta-hemolysis under iron-rich and iron-limiting conditions. Beta-hemolysis was suppressed in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…The growth medium was TSBYE (3% tryptic soy broth plus 0.6% yeast extract) containing, when needed to select for transformants, spectinomycin (Spec) to a final concentration of 100 g/ml or ampicillin to a final concentration of 10 g/l. In experiments where leukotoxin protein levels were evaluated, 300 M FeCl 3 was included in the medium to suppress leukotoxin secretion (39).…”
Section: Methodsmentioning
confidence: 99%
“…The growth medium was TSBYE (3% tryptic soy broth plus 0.6% yeast extract) containing, when needed to select for transformants, spectinomycin (Spec) to a final concentration of 100 g/ml or ampicillin to a final concentration of 10 g/l. In experiments where leukotoxin protein levels were evaluated, 300 M FeCl 3 was included in the medium to suppress leukotoxin secretion (39).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, JP2 strains have an impaired ability to utilize complexed iron from host proteins. We have proposed that perhaps high leukotoxicity (and hence deletion of the promoter region) was strongly selected for in these strains that lacked HgpA, resulting in the JP2 phenotype (Balashova et al, 2006b). Increased lysis of RBCs would result in greater release of heme and hemoglobin and a more favorable chance that some could be used by the bacterium.…”
Section: Ironmentioning
confidence: 99%
“…Indeed, iron regulates secretion, not transcription, of LtxA (Balashova et al, 2006b). In the presence of excess iron, but not other metal ions, LtxA remains intracellular; but under iron-limiting conditions, LtxA is essentially fully secreted.…”
Section: Ironmentioning
confidence: 99%
“…In addition, we have recently shown that LtxA can act as a hemolysin that may be used during systemic infection for acquiring iron from the host (2). Indeed, iron, but not other metals, regulates LtxA secretion in A. actinomycetemcomitans (3).…”
mentioning
confidence: 99%